Thermo‐catalytic conversion of greenhouse gases (CO2 and CH4) to CO‐rich hydrogen by CeO2 modified calcium iron oxide supported nickel catalyst - Hossain, Mohammed Anwar; Ayodele, Bamidele V.; Ong, Huei Ruey; Siti I., Mustapa; Cheng, C. K.; Khan, Maksudur R. (Wiley Online Library, 2020)
In this study, the thermo‐catalytic conversion of two principal greenhouse gases (methane and carbon dioxide) to carbon monoxide (CO)‐rich hydrogen (H2) is investigated over cerium oxide (CeO2) promoted calcium ferrite supported nickel (Ni/CaFe2O4) catalyst. The CeO2 promoted Ni/CaFe2O4 catalyst was prepared using wet‐impregnation technique. To ascertain the physicochemical properties, the as‐prepared catalyst was characterized using various instrument techniques. The characterization of the catalysts reveals that CeO2‐Ni/CaFe2O4 possesses suitable physicochemical properties for the conversion of methane (CH4) and carbon dioxide (CO2) to CO‐rich H2. The thermo‐catalytic reaction revealed that the CeO2 promoted Ni/CaFe2O4 catalyst displayed a higher CH4 and CO2 conversions of 90.04% and 91.2%, respectively, at a temperature of 1073 K compared to the unpromoted catalyst. The highest H2 and CO yields of 78% and 76%, respectively, were obtained over the CeO2‐Ni/CaFe2O4 at 1073 K and CH4/CO2 ratio of 1. The CeO2 promoted Ni/CaFe2O4 catalyst remained stable throughout the 30 hours time on stream (TOS) while that of the unpromoted Ni/CaFe2O4 catalyst sharply decreased after 22 hours TOS. The characterization of the used catalysts confirms the evidence of carbon depositions on the unpromoted Ni/CaFe2O4 which is solely responsible for its deactivation. Whereas, there was a slightly gasifiable carbon deposited on the CeO2 promoted Ni/CaFe2O4 catalyst which could be ascribed to the interaction effect of the CeO2 promoter on the Ni/CaFe2O4 catalyst.